2016
DOI: 10.1186/s40064-016-3209-y
|View full text |Cite
|
Sign up to set email alerts
|

Carotid blowout syndrome after nasopharyngeal carcinoma radiotherapy: successful treatment by internal carotid artery occlusion after stent implantation failure

Abstract: IntroductionCarotid blowout syndrome (CBS) secondary to radiation therapy is life-threatening and requires emergency treatment. More recently, endovascular treatment has provided an effective way to control CBS-related bleeding.Case descriptionWe present a case of CBS with a rupture of the internal carotid artery (ICA) pseudo-aneurysm after Gamma Knife radiation therapy for nasopharyngeal carcinoma (NPC). The patient was a 55-year-old man who was transferred to our hospital with severe repetitive epistaxis. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…2 Multidisciplinary and standardized treatment paths are crucial for mastering the quick selection of the appropriate treatment strategy, which must be patient-specific. 3,4 Radiological interventions, such as angiographic embolization or stenting, are first-line treatments for CBS. Recent advances have created a noninvasive, lifesaving alternative to the challenging procedure of open surgical ligation of the carotid arteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Multidisciplinary and standardized treatment paths are crucial for mastering the quick selection of the appropriate treatment strategy, which must be patient-specific. 3,4 Radiological interventions, such as angiographic embolization or stenting, are first-line treatments for CBS. Recent advances have created a noninvasive, lifesaving alternative to the challenging procedure of open surgical ligation of the carotid arteria.…”
Section: Introductionmentioning
confidence: 99%
“…Immediate clinical assessment including digital subtraction angiography is required for diagnosing CBS . Multidisciplinary and standardized treatment paths are crucial for mastering the quick selection of the appropriate treatment strategy, which must be patient‐specific . Radiological interventions, such as angiographic embolization or stenting, are first‐line treatments for CBS.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, stents cannot be successfully implanted in all patients. Stent implantation was treated as the first choice but failed because of moderate lumen stenosis and the emergent massive bleeding in the procedure caused by weak vascular structure, at this moment ICA occlusion can be a choice (Dong et al, 2016). Choi suggested that the protection of ICA during IMRT could decrease the risk of atherosclerosis, and IMRT is still the priority treatment for recurrent head and neck cancer (Choi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to the widespread recognition of carotid pseudoaneurysm and subsequent “blowout” in the neck following RT for metastatic cervical disease, 1 the potential for sinonasal pseudoaneurysm is less well recognized in spite of being described in the literature as a possible complication of RT for NPC. 2,3 In certain cases, a sentinel bleeding event may alert the clinician to this possibility (ie, case 2). However, some sentinel bleeding events may be mistaken for the more common mucosal irritation related to CRT causing epistaxis, thus putting the patient at risk for a catastrophic event (ie, case 1).…”
Section: Discussionmentioning
confidence: 99%
“…5 Advanced endovascular techniques have made the treatment of carotid artery or other major arterial pseudoaneurysms more successful and safer for patients, presuming that they are identified before a catastrophic bleeding event occurs. 2,3 Maintaining a high suspicion of a potential underlying pseudoaneurysm is the key in this patient population.…”
Section: Discussionmentioning
confidence: 99%